Application of polymer composites in the design of agricultural machines for tillage - Aulin, V.V.; Derkach, O.D.; Makarenko, D.O.; Hrynkiv, A.V.; Krutous, D.I. (Problems of Tribology, 2020)
The article includes an analysis of the state of production of crop production in Ukraine and a description of the shortcomings in the work of cultivators.It was proposed to modernize the construction of cultivators with the help of polymer composite materials. We recommend the introduction of a polymer composite CCPA-6-30 in the construction of cultivators, it has high tribotechnical characteristics